2014
DOI: 10.1118/1.4892600
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dosimetry in digital breast tomosynthesis: Report of AAPM Tomosynthesis Subcommittee Task Group 223

Abstract: The radiation dose involved in any medical imaging modality that uses ionizing radiation needs to be well understood by the medical physics and clinical community. This is especially true of screening modalities. Digital breast tomosynthesis (DBT) has recently been introduced into the clinic and is being used for screening for breast cancer in the general population. Therefore, it is important that the medical physics community have the required information to be able to understand, estimate, and communicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 24 publications
1
44
0
2
Order By: Relevance
“…Examined breasts, using the methods by Dance et al [12], or ACR [30], which uses the model developed by Wu et al [31,32] as a basis for breast dosimetry. These methods are integrated into clinical systems.…”
Section: Resultsmentioning
confidence: 99%
“…Examined breasts, using the methods by Dance et al [12], or ACR [30], which uses the model developed by Wu et al [31,32] as a basis for breast dosimetry. These methods are integrated into clinical systems.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, the American Association of Physicists in Medicine (AAPM) published Task Group Report #223 on radiation dosimetry in DBT in which the Wu et al model for mammography was extended for breast tomosynthesis (Sechopoulos et al , 2014). For this, the concept of the RGD(α) and system-specific mean RGD (denoted trueRGD¯) were used and the values for a generic system and for five commercial and prototype systems are provided.…”
Section: Conversion Factors For Dbt Using Simple Geometrical Modelmentioning
confidence: 99%
“…Dance et al (76) provided a DBT system-specific factor in determining MGD as per United Kingdom, European, and IAEA protocols. A recent task group report from the American Association of Physicists in Medicine provided similar factors for each DBT system (77). Dosimetry of a system capable of DBT and FFDM acquisitions using the automated exposure control mechanism showed that in general, the MGD from DBT was higher than that from FFDM (77).…”
Section: Radiation Dosementioning
confidence: 99%
“…A recent task group report from the American Association of Physicists in Medicine provided similar factors for each DBT system (77). Dosimetry of a system capable of DBT and FFDM acquisitions using the automated exposure control mechanism showed that in general, the MGD from DBT was higher than that from FFDM (77). For the combined DBT plus FFDM mode (hereafter, DBT-FFDM), the MGD determined as per dosimetry protocol used in the United States was lower than the regulatory limit of 3 mGy for a CC-equivalent view of an average breast (78).…”
Section: Radiation Dosementioning
confidence: 99%